Efektivitas Pelayanan Informasi Publik oleh PPID terkait Program Pemberdayaan Sosial di Dinas Sosial Provinsi - Rynesa Gresela Putri; Anti Wulan Agustini (Lembaga Pengembangan Kinerja Dosen, 2026)
Community service is a form of implementation of the Tri Dharma of Higher Education which aims to make a real contribution to society through the application of science and technology. This activity was carried out to increase public understanding of the effectiveness of public information services managed by the Information and Documentation Management Officer (PPID) related to social empowerment programs at the Provincial Social Service. The method used in this service activity is a descriptive approach with observation, counseling, discussion, and documentation techniques. The results of the activity show that public information services have an important role in increasing information disclosure and making it easier for the public to obtain information about various social empowerment programs organized by the government. Through counseling and discussion activities, the community becomes more aware of the procedures for obtaining public information and the importance of information disclosure in supporting community participation. In addition, this activity also increases public awareness of the right to obtain information and encourages transparency and accountability in the implementation of public services. Thus, the effectiveness of public information services can support the creation of good governance.